Crystalline and Non-crystalline Solids - Mandracci, Pietro (IntechOpen, 2016)
The structural properties of materials play a fundamental role in the determination of their suitability for a specific application. This book is intended as a contribution to the efforts to increase the knowledge of the influence exerted on the properties of materials by their crystalline or amorphous structure. To this aim, some of the materials that are most promising for their use in different technological fields have been studied, namely graphene, titanium oxide, several types of functional metal oxides, porphyrinic crystalline solids, plasma deposited polymers, amorphous silicon, as well as hydrogenated amorphous carbon. These materials have been presented by the authors for their use in different applications, including microelectronics, photonics, and biomedicine.